THE MEDIATING ROLE OF FINANCIAL LITERACY ON THE EFFECT OF FINANCIAL ATTITUDE AND ACCOUNTING INFORMATION SYSTEMS ON BUSINESS SUSTAAINAABILITY ( A STUDY OF MSMEs IN GORONTALO CITY) - Lutfiah Wanda Hiola; Tri Handayani Amaliah; Usman (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to examine the effect of financial attitude and accounting information systems on business sustainability, with financial literacy as a mediating variable, among Micro, Small, and Medium Enterprises (MSMEs) in Gorontalo City. This research adopts a quantitative approach using a causal survey design. Data were collected through questionnaires distributed to 100 MSME owners in Gorontalo City and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that financial attitude has a positive and significant effect on business sustainability. Meanwhile, accounting information systems do not have a significant direct effect on business sustainability. Furthermore, financial literacy is not able to mediate the relationship between financial attitude and business sustainability. However, financial literacy significantly mediates the relationship between accounting information systems and business sustainability. These findings suggest that business sustainability among MSMEs is strongly influenced by internal financial behavior and competencies. Financial literacy plays a crucial role in transforming accounting information into meaningful managerial decisions that support long-term business sustainability. This study contributes to the Resource-Based View (RBV) theory by highlighting financial literacy as a strategic intangible resource for MSMEs.